(untitled) (Progressive Agriculture, 2019)
Storage of rice is crucial postharvest operation. Traditional rice storage structures vary over local resources, climate and culture in Bangladesh. This study was carried out to investigate the efficacy of diversified rice storage structures at farmer’s level. Household survey was conducted through face to face interview of farmers using developed pretested questionnaire. Rice samples were also collected to test the quality of stored rice. Six different types of traditional structures namely Dole, Steel drum, Plastic bag, Plastic drum, Gunny bag and Motka for rice storage were identified. Maximum insect infestation in stored rice was observed in Dole followed by Motka, Plastic Bag and Plastic drum. This may be due to upper surface of Dole was open. Germination capacity went down to 68% in Plastic bag, 55% in Motka, and 80% in Plastic drum. Rice storage in Plastic drum was found effective in terms of insect infestation and germination capacity in comparison with other traditional storage structures Motka, Dole and Plastic bag. Therefore, Plastic drum can be an alternative option in rice storage. Progressive Agriculture, Vol. 30, Suppl. 1: 51-56, 2019